The gains in life expectancy by ambient PM2.5 pollution reductions in localities in Nigeria. (May 2018) - Etchie, Tunde O.; Etchie, Ayotunde T.; Adewuyi, Gregory O.; Pillarisetti, Ajay; Sivanesan, Saravanadevi; Krishnamurthi, Kannan; Arora, Narendra K.
Abstract: Global burden of disease estimates reveal that people in Nigeria are living shorter lifespan than the regional or global average life expectancy. Ambient air pollution is a top risk factor responsible for the reduced longevity. But, the magnitude of the loss or the gains in longevity accruing from the pollution reductions, which are capable of driving mitigation interventions in Nigeria, remain unknown. Thus, we estimate the loss, and the gains in longevity resulting from ambient PM2.5 pollution reductions at the local sub-national level using life table approach. Surface average PM2.5 concentration datasets covering Nigeria with spatial resolution of ∼1 km were obtained from the global gridded concentration fields, and combined with ∼1 km gridded population of the world (GPWv4), and global administrative unit layers (GAUL) for territorial boundaries classification. We estimate the loss or gains in longevity using population-weighted average pollution level and baseline mortality data for cardiopulmonary disease and lung cancer in adults ≥25 years and for respiratory infection in children under 5. As at 2015, there are six "highly polluted", thirty "polluted" and one "moderately polluted" States in Nigeria. People residing in these States lose ∼3.8–4.0, 3.0–3.6 and 2.7 years of life expectancy, respectively, due to the pollution exposure. But, assuming interventions achieve global air quality guideline of 10 μg/m 3, longevity would increase by 2.6–2.9, 1.9–2.5 and 1.6 years for people in the State-categories, respectively. The longevity gains are indeed high, but to achieve them, mitigation interventions should target emission sources having the highest population exposures. Graphical abstract: Estimate of the loss in life expectancy attributed to ambient PM2.5 pollution exposure, and the gains accruing from attainment of the global air quality guideline of 10 μg/m 3 ; in States and in Nigeria as a whole.Image 1 Highlights: We estimate loss/gains in longevity from PM2.5 pollution in Nigerian localities. The pollution reduced longevity by 3.5 (range = 2.4–4.1) years. Attainment of WHO AQG can increase longevity by 2.4 (1.3–3.0) years. Emission sources with the highest exposures should be prioritized.